Azure Arc-enabled data services revealed early first edition based on public preview - Weissman, Benjamin (Apress, 2022)
Get introduced to Azure Arc-enabled data services and the powerful capabilities they provide to deploy and manage local, on-premises, and hybrid cloud data resources using the same centralized management and tooling you get from the Azure cloud. This book shows how you can deploy and manage databases running on SQL Server and Posgres in your corporate data center as if they were part of the Azure platform. You will learn how to benefit from the centralized management that Azure provides, the automated rollout of patches and updates, and more. This book is the perfect choice for anyone looking for a hybrid or multi-vendor cloud strategy for their data estate. The authors walk you through the possibilities and requirements to get services such as Azure SQL Managed Instance and PostgresSQL Hyperscale, deployed outside of Azure, so the services are accessible to companies that cannot move to the cloud or do not want to use the Microsoft cloud exclusively. The technology described in this book will be especially useful to those required to keep sensitive services, such as medical databases, away from the public cloud, but who still want to benefit from the Azure cloud and the centralized management and tooling that it supports. What You Will Learn Understand the core concepts of Kubernetes Understand the fundamentals and architecture of Azure Arc-enabled data services Build a multi-cloud strategy based on Azure data services Deploy Azure Arc-enabled data services on premises or in any cloud Deploy Azure Arc-enabled SQL Managed Instance on premises or in any cloud Deploy Azure Arc-enabled PostgreSQL Hyperscale on premises or in any cloud Manage Azure-enabled data services running outside of Azure Monitor Azure-enabled data services running outside of Azure through the Azure Portal Who This Book Is For Database administrators and architects who want to manage on-premises or hybrid cloud data resources from the Microsoft Azure cloud. Especially for those wishing to take advantage of cloud technologies while keeping sensitive data on premises and under physical control.
Includes index. - Print version record
Keywords: Microsoft Azure (Computing platform); Cloud computing; Infonuagique; Microsoft Azure (Plateforme informatique)